Dampak kehilangan gigi, fungsi kognitif dan kualitas hidup lanjut usia - Sri Setyowati; Parmadi Sigit Purnomo; Masti Hartina (STIKes Surya Global Yogyakarta, 2021)
Tooth loss has an impact on aspects of the life of the elderly. Cognitive function and quality of life of the elderly can be impaired. This study aims to determine the relationship between tooth loss with cognitive function and quality of life in the elderly. This quantitative study used a correlational design. The study population was all elderly people who experienced tooth loss at the Budi Dharma Social Service Home for the Abandoned Elderly Yogyakarta with a total population of 58 people. Non-probability sampling technique with purposive sampling method was used to determine the sample. Inclusion criteria were elderly people aged 60 years and over, experienced tooth loss, and were willing to be respondents. While the exclusion criteria were the elderly who did not experience mental disorders, who wore dentures and did not fully participate in the study. And with the slovin formula in getting as many as 51 respondents. Data collection techniques were interview and observation using the instrument of the observation table for tooth loss, the SPMSQ questionnaire to measure cognitive function and the WHOQOL questionnaire to measure quality of life. Correlation test using Kendall tau. The results showed that the majority of respondents were women (62.7%) in the age range of 60-78 years (78.4%) with no school status (68.6%). The highest number of tooth loss was in respondents aged 60-78 years with a total loss of 21-32 teeth (41.3%), experiencing moderate decline in cognitive function (49%) and poor quality of life (62.7%). The results of the correlation test showed that there was a relationship between tooth loss and cognitive function with a p-value of 0.000. There is a relationship between tooth loss and quality of life with a p-value of 0,000. The conclusion of this study is that there is a significant relationship between tooth loss with cognitive function and quality of life in the elderly at the Budi Dharma Abandoned Elderly Social Service Home, Yogyakarta.